The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.amepre.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status Measures Collected in the Healthy Communities Study

Abstract: The Healthy Communities Study is one of the largest studies to assess the relationship between characteristics of community programs and policies to prevent childhood obesity and obesity-related outcomes. The purpose of this paper is to describe the protocol that was developed for collecting the anthropometric data for the study and the procedures for analyzing the data. Data were collected from 2013 to 2015 and analyses will be completed by mid-2016. During in-home visits, Healthy Communities Study staff coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Participants underwent a standard protocol to measure child height, weight, and waist circumference and information collection on demographic and background characteristics and nutrition and physical activity behaviors. 18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants underwent a standard protocol to measure child height, weight, and waist circumference and information collection on demographic and background characteristics and nutrition and physical activity behaviors. 18 …”
Section: Methodsmentioning
confidence: 99%
“…18 Measures were taken twice and entered into the information management system, which checked for data quality (e.g., plausible values). Data quality was achieved through training and certification of field staff, repeated measurement, presence of supervising staff during selected in-home visits, and post-visit review of data.…”
Section: Methodsmentioning
confidence: 99%
“…With these outcomes observed on a large sample of children, data can be combined across communities to identify the program and policy attributes that are most closely associated with child outcomes at different stages of development. Power calculations demonstrated that the study can detect 4.9%–7.5% differences in current BMI associated with current indices of community-based program and policy intensity using cross-sectional models, and BMI change differences of less than 1% by combining longitudinal measures of BMI from medical records 18 with longitudinal indices of community-based program and policy intensity. 17 …”
Section: Planned Statisical Analysis Of Datamentioning
confidence: 97%
“…standard protocol: current height/weight status of child, questionnaires from parent/child on physical activity and diet, and medical record abstraction to develop longitudinal BMI trajectories from entire sample 18–20 ;…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation